PENGARUH LATIHAN AEROBIK TERHADAP FORCED VITAL CAPACITY (FVC)PRIA DEWASA DENGANOVERWEIGHT - Sagay, Ester Florencia; Polii, Hedison; Wungouw, Herlina I. S. (Universitas Sam Ratulangi, 2013)
Abstract: Changes to respiratory function due to regular aerobic exercise will affect the value of pulmonary function, especially in Forced Vital Capacity (FVC). This research aimed to determine the effect of aerobic exercise on FVC overweight male students of Unsrat Medical Faculty. This research is analytic with design experimental, one group pre and post test design. The sampling technique used is non-purposive sampling technique. The research sample was taken from the students of the Faculty of Medicine 2009, Univercity of Sam Ratulangi who fulfill the inclusion criteria. Some 32 students were selected as research subjects. After giving informed consent, FVC measurement was done with the spirometer. After it was measured, they were given treatmen in the form aerobic exercise using a stationary bike for three weeks with frequency of exercise three times a week and exercise intensity for 30 minutes. We measured again FVC values after the exercise three times program. Normality test data showed significance for FVC value before treatment by 0.752, and after treatment by 0.912. Comparison of the average value before and after exercise were tested by using a paired test. Significant value for FVC is P = 0.084, means there is no significant difference between FVC values before and after exercise (P> 0.05). The mean FVC was 3.88 before treatment and after treatment the mean value was 4.00, an increase in the average value of 0.11. Conclusion:Aerobic Exercise on a regular basis using a stationary bike on the overweight male student can improve lung function in particular the mean FVC but there was no significant difference from the mean value. Keywords: FVC, Aerobic Exercise, Overweight. Abstrak: Perubahan fungsi pernapasan karena latihan aerobik secara teratur akan mempengaruhi nilai fungsi paru khususnya Forced Vital Capacity (FVC). Penelitian ini untuk mengetahui pengaruh latihan aerobik terhadap FVC mahasiswa pria Fakultas Kedokteran Unsrat dengan berat badan lebih.Penelitian ini bersifat analitik dengan rancangan eksperimental one grup pre and post test design. Pengambilan sampel dilakukan dengan teknik non purposive sampling. Sampel penelitian diambil dari Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Angkatan 2009.Sejumlah 32 orang mahasiswa terpilih sebagai subjek penelitian dan dilakukan pengukuran FVC dengan Spirometer.Setelah itu diberikan perlakuan berupa latihan aerobik menggunakan sepeda statis selama tiga minggu dengan frekuensi latihan tiga kali seminggu dan intensitas latihan selama 30 menit.Selanjutnya dilakukan pengukuran kembali nilai FVC sesudah program latihan.Uji normalitas data menunjukkan nilai signifikansi untuk FVC sebelum perlakuan sebesar 0.752, dan sesudah perlakuan sebesar 0.912. Perbandingan nilai rata rata sebelum dan sesudah latihan diuji dengan menggunakan uji t berpasangan.Nilai signifikan untuk FVC adalah P = 0.084, berarti tidak terdapat perbedaan yang bermakna antara nilai FVC sebelum dan sesudah latihan (P > 0.05) .Nilai rerata FVC sebelum pelakuan adalah 3,88 dan nilai rerata sesudah perlakuan adalah 4,00, terjadi penigkatan nilai rerata sebesar 0,11.Simpulan:Latihan Aerobik menggunakan sepeda statis secara teratur dapat meningkatkan nilai rerata fungsi paru khususnya FVC tetapi tidak terdapat perbedaan yang bermakna dari nilai rerata tersebut. Kata Kunci: FVC, Latihan Aerobik, Berat Badan Lebih (Overweight).